The Vicious Cycle and False Consciousness in The Fast Saga - Grishiella Patricia Liwang (Fakultas Ilmu Komunikasi UKWMS, 2023)
Films addressing sports/racing themes have been extensively released, and one of the successful franchises is the Fast Saga franchise. Within the media text of The Fast Saga, there's criticism regarding how female characters are depicted as weak and having little knowledge about racing, which is more associated with males. This study aims to reveal the discourse of masculine hegemony within The Fast Saga. The theoretical focus used in this research is hegemonic masculinity, employed to examine the gender practice configuration between men and women. This research is divided into three sub-discussions: gender domination, sexual objectification, role differentiation, and gender relations. Within these focuses, the author was able to uncover imbalances in these three sub-discussions through Sara Mills' critical discourse analysis as the research method. Sara Mills' critical discourse analysis will examine how the subject-object positions are placed within the text through eight films divided into 10 scenes. The research findings involving The Fast Saga show that despite women attempting to portray toughness in racing, hegemony is still apparent in those scenes. In reality, The Fast Saga continues to display forms of masculine hegemony and reinforces them as if they are the only values worth upholding.ABSTRAK Film-film yang mengangkat tema mengenai sport/racing telah banyak dirilis, dan salah satu franchise yang sukses adalah Fast Saga franchise. Dalam teks media The Fast Saga, terdapat kritik terhadap bagaimana karakter perempuan digambarkan lemah dan memiliki sedikit pengetahuan tentang balap yang lebih berhubungan dengan laki-laki. Penelitian ini bertujuan mengungkap wacana hegemoni maskulinitas dalam The Fast Saga. Fokus teori yang digunakan dalam penelitian ini adalah hegemoni maskulinitas, yang digunakan untuk mengkaji konfigurasi praktik gender antara hubungan laki-laki dan perempuan. Penelitian ini dibagi menjadi tiga sub pembahasan yakni dominasi gender, objektifikasi seksual, diferensiasi peran dan relasi gender. Dalam fokus tersebut, penulis mampu menemukan ketimpangan yang terjadi mengenai tiga sub pembahasan tersebut dengan analisis wacana kritis Sara Mills sebagai metode penelitiannya. Analisis wacana kritis Sara Mills akan melihat bagaimana posisi subjek-objek ditempatkan dalam teks melalui delapan film yang dibagi menjadi 10 adegan. Hasil penelitian dengan subjek The Fast Saga ini menemukan bahwa hegemoni masih nampak dalam adegan-adegan tersebut meski perempuan sudah berusaha menampilkan ketangguhan dalam balapan. Pada kenyataannya The Fast Saga tetap menampilkan bentuk-bentuk hegemoni maskulinitas dan menegaskannya seolah-olah hanya itu nilai yang patut dijunjung.